Profiles, Challenges, and Motivations of Science YouTubers - Velho, Raphaela M.; Barata, Germana (Frontiers in Communication, 2020)
This paper investigates the profiles, challenges and motivations of science communicators of the ScienceVlogs Brasil project – a Brazilian alliance of YouTube channels that disseminate science information on YouTube. It also looks into their prospects of professionalization in science communication and their strategies to improve their skills, increase public reach and have financial support. Results show that the typical science YouTuber is a highly educated young male who works primarily in the education field, wishes to improve science understanding and fight misinformation, and is challenged by YouTube’s highly competitive environment and restrictive algorithms. Science YouTubers also strive to improve their skills and techniques to produce high-quality, professional-like videos to become visible on the platform.